1981
DOI: 10.1677/joe.0.0900403
|View full text |Cite
|
Sign up to set email alerts
|

Development of Hypothalamic–pituitary–adrenal Response to Stress in Rats Made Hypothyroid by Exposure to Thiouracil From Conception

Abstract: The functional maturation of the hypothalamic-pituitary-adrenal (HPA) axis has been studied in rats of 20-35 days of age made hypothyroid by the administration of thiouracil from conception. Basal concentrations of corticosterone in serum were normal in hypothyroid animals. Ether stress led to an increase corticosterone content of the adrenal glands of hypothyroid and normal rats but not to a rise in serum corticosterone of hypothyroid rats until 30 days of age. Corticosterone secretion in response to ACTH adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1

Year Published

1983
1983
1992
1992

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
1
2
1
Order By: Relevance
“…Thus, neonatal Tj administration re sults in an early increase in basal corticosterone titers and CBG levels [6,10,22] as well as in the early maturation of the adrenocortical response to stress [29]. In contrast, PTU administration during this period delays the maturation of the adrenocortical stress response and suppresses CRF-like activity in the hypothalamus [23,24]. These effects are con sistent with the effects on glucocorticoid receptor concen trations reported here.…”
Section: Discussionsupporting
confidence: 75%
“…Thus, neonatal Tj administration re sults in an early increase in basal corticosterone titers and CBG levels [6,10,22] as well as in the early maturation of the adrenocortical response to stress [29]. In contrast, PTU administration during this period delays the maturation of the adrenocortical stress response and suppresses CRF-like activity in the hypothalamus [23,24]. These effects are con sistent with the effects on glucocorticoid receptor concen trations reported here.…”
Section: Discussionsupporting
confidence: 75%
“…We hypothesized that if 5-HT (or DA) did mediate central inhibition of ACTH release, then the hypothyroid model might show inhibition of ACTH/corticosterone response to stress. It has been previously shown that neonatal hypothyroid 1070 SMYTHE, BRADSHAW, AND VINING Endo • 1983 Volll3«No3 rats have reduced corticosterone responses to stress (29). However, in the present study, ACTH and corticosterone responses after either cold swim or ether stress in adult hypothyroid rats were comparable to the responses of normal adult rats.…”
Section: Discussioncontrasting
confidence: 62%
“…Specifically, the developmental increase in this parameter was advanced approximately 3 days in hyperthyroid animals and was delayed approximately 3 days in hypothyroid animals. Previous studies on the effects of T4 status on the in vivo response of serum corticosterone to ACTH yielded conflicting results (22)(23)(24) and their interpretation was complicated by the use of a fluorometric assay which is known to be inappropriate in young rodents (1,…”
Section: Age (Days)mentioning
confidence: 99%